Hubungan Antara Karakteristik Individu, Paparan Debu Asap Las (Welding Fume) dan Gas Karbon Monoksida (CO) Dengan Gangguan Faal Paru Pada Pekerja Bengkel Las (Studi di Kelurahan Ngagel Kecamatan Wonokromo Surabaya) The Correlation Between Individual Characteristic, Exposure of Welding Fumes and Carbon Monoxide With Pulmonary Function Disorder of Welding Workers (Study in Ngagel Village, Wonokromo Sub district, Surabaya) - Ahmad Aris Febrianto; Anita Dewi Prahastuti Sujoso; Ragil Ismi Hartanti (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Welding industries are prone to hazards. Welding fumes and carbon monoxide resultedfrom the welding process can cause pulmonary function disorder. Based on the surveyof welding station in Ngagel, there were 7 workers exposed to pulmonary functiondisorder. This study aimed to analyze the relationship between individual characteristic,welding fumes and carbon monoxide (CO) with pulmonary function disorder of weldingworkers in Ngagel Village, Wonokromo, Surabaya. This study is observational analyticwith cross sectional approach and sample of 36 workers from 5 welding station. Theresult of this studied that there were relationship between pulmonary function disorderand welding fumes, individual characteristics in terms of age, duration of exposure,working periode, cigarette smoke, and the amount of cigarette and not correlatedbetween nutrional status, temperature, humadity with pulmonary function disorder.Keywords: welding fume, carbon monoxide, individual characteristic, work climate,pulmonary function disorder.